2003
DOI: 10.1097/00042737-200304000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 expression and apoptotic activity of Helicobacter pylori positive and negative gastritis in correlation with the presence of intestinal metaplasia

Abstract: In the absence of intestinal metaplasia H. pylori infection increases both apoptotic activity and expression of p53 oncoprotein in the gastric mucosa. The lack of increased apoptosis with a higher p53 expression in the presence of intestinal metaplasia suggests an increased genetic instability and also may suggest that mutation of the p53 gene is an early step in the multistep process of gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
4
15
0
4
Order By: Relevance
“…[32] demonstrated that the expression of p53 and apoptotic indices in gastritis in the absence of intestinal metaplasia are significantly higher in H pyloripositive patients than in H pylori-negative patients. These studies are in agreement with our results indicating that in some p53 mutations are found mutant type-p53 products in the H pylori-infected gastric pits.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[32] demonstrated that the expression of p53 and apoptotic indices in gastritis in the absence of intestinal metaplasia are significantly higher in H pyloripositive patients than in H pylori-negative patients. These studies are in agreement with our results indicating that in some p53 mutations are found mutant type-p53 products in the H pylori-infected gastric pits.…”
Section: Discussionmentioning
confidence: 97%
“…Our results indicated that while the majority of cells that reacted with p53 (DO-7) account for an accumulation of wild-type p53, mutant type p53 might also be expressed in some cells of the gastric pit. Murakami et al [14] and Morgan et al [31] reported the presence of point mutations in exon 5 to 8 of p53 in H pylori-positive gastritis, and several other studies have shown that gastric precancerous lesions, such as atrophic gastritis and intestinal metaplasia, are associated with p53 abnormalities [20][21][22]26,32] . Murakami et al [14] reported that the point mutations are present in 52.4% of the gastritis, with Morgan et al [31] reporting the presence of p53 mutations in 35% of the gastritis and 45% of the intestinal Figure 2 Labeling indices for p53 (DO-7) in 42 patients with H pylori infection, 6 mo after eradication, and 11 patients without H pylori infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…frequent in gastric cancer. In addition, p53 mutations are also observed in intestinal metaplasia (38%) and gastric dysplasia (58%), suggesting that mutations of the p53 gene may be an early event and perhaps work together with RAS oncogene in the pathogenesis of gastric cancer [9]. Further evidence for a role of p53 in the early stages of gastric cancer development comes from studies in mice that are hemizygous for p53, which display an increased proliferative response to H. pylori infection compared with wild-type mice.…”
Section: Colon Stomach Esophagusmentioning
confidence: 99%
“…The best studied and most common oncogene alteration in colonic neoplasm involves the RAS oncogene, which also works together with p53 gene mutation in gastric carcinogenesis [9] and up-regulates the gene expression of gastrin. The latter is an oncogenic growth factor contributing to gastric and colon carcinogenesis [6,19].…”
Section: Hypergastrinemia and H Pylori Infectionmentioning
confidence: 99%